Anti-NMDAR encephalitis in Crohn’s disease undergoing long-term infliximab treatment: A case report - Oh, Shin Ju; Kwon, Young Nam; Lee, Chang Kyun; Lee, Jin San (Frontiers in Immunology, 2022)
Infliximab, a chimeric monoclonal antibody against anti-tumor necrosis factor-α (TNF-α), has revolutionized the management of inflammatory bowel disease. However, a recent nested case-control study showed that anti-TNF-α therapy exposure in patients with autoimmune diseases is associated with an increased risk of inflammatory central nervous system (CNS) events. A 27-year-old man diagnosed with Crohn’s disease at 17 years of age was referred to our clinic for suffering with Wernicke’s aphasia and the right-hand weakness over two weeks. Nine years of treatment for Crohn’s disease with infliximab anti-TNF-α therapy was well tolerated. An initial MRI revealed diffuse leptomeningeal enhancement along the bilateral cerebral sulci without any parenchymal abnormalities. Cerebrospinal fluid (CSF) and serum N-methyl-D-aspartate receptor (NMDAR) antibody testing yielded positive results. Anti-NMDAR encephalitis was diagnosed, and the patient was treated with rituximab. A follow-up brain MRI showed new multiple cerebral lesions in the left insular cortex and subcortical white matter of the left frontal and temporal gyri. Approximately 8 months after symptom onset, the CSF and serum NMDAR antibody converted to negative. Twelve months later, the patient fully recovered from anti-NMDAR encephalitis without any neurological deficits and is currently being treated with the anti-interleukin 12/23 agent ustekinumab for Crohn’s disease. This is the first report of not only a patient with infliximab-associated anti-NMDAR encephalitis in Crohn’s disease but also of an inflammatory non-demyelinating CNS event during long-term suppression of TNF-α. Our case highlights the need for clinicians to recognize the possibility of a paradoxical autoimmune response occurring with novel biological therapies.